Fiscal Reconciliation Analysis of Commercial Financial Statements - Octavianty, Ellyn; Ilmiyono, Agung Fajar; Indrayono , Yohanes; Hutasoit, Mei (Westscience Press, 2025)
Fiscal reconciliation is carried out to overcome the difference in perception between accounting by determining the taxation of income and expense accounts. The purpose of this study is to find out whether the fiscal correction is appropriate based on the tax provisions on income and expense accounts in the financial statements. To find out the basis for calculating taxable income as the basis for calculating taxes payable and to find out how to prepare a fiscal reconciliation report in more detail. This research was conducted on Agricultural Sub-Sector Companies listed on the Indonesia Stock Exchange in 2019-2023. The sample used in this study is 4 companies, namely PT Bisi International Tbk, PT PP London Sumatra Indonesia Tbk, PT Sinar Mas Agro Resources and Technology Tbk and PT Tunas Baru Lampung Tbk. The sample selection uses the purposive sampling method with the analysis method used, namely descriptive and comparative with the empirical study method, which describes a phenomenon/event systematically as it is. The results of the research on fiscal corrections made by agricultural sub-sector companies on income and expense accounts are in accordance with applicable tax regulations. After the fiscal reconciliation of the commercial income statement, it results in changes in the company's taxable income due to differences in recognition, namely fixed differences and time differences according to commercial and fiscal. So that there is a change in the company's tax burden, from the difference in recognition, there is an increase and decrease in the amount of taxable income so that the company experiences underpayment and overpayment of the company's outstanding taxes.